(untitled) (Fiep Bulletin - online, 2014)
The present work is based on a reflection about physical activity as a leisure alternative and a way to enhance quality of life. Firstly, the theoretical underpinnings of quality of life were discussed, focusing on the importance of a physically active life with quality. Secondly, the program "UTFPR in action" was presented together with its objectives concerning quality of life and leisure. This study focuses on the fallowing aspects: self-evaluation of the quality of life of the participants, the importance of leisure activities as a way to promote quality of life, and the influence of the program on the participants’ lives. The survey was based on a sample of 77 participants (55% of the population). They answered a set of questions which provided the basis for a discussion of the overall results obtained as well as a critical assessment of the program, which proved to be effective.